Analysis of English Language Test Tasks for the Fifth and Sixth Graders in Serbia according to Bloom's Taxonomy - Tatjana Lj. Glušac; Isidora M. Wattles (University of Belgrade, Teacher Education Faculty, 2020)
Critical thinking (CT) is a vital academic and life skill. Its development begins early in life, but it needs to be cultivated both during and after one's education. In school, CT can be taught both within the domain of different subjects or as a separate skill. For it to be properly taught, CT needs to be assessed. With that in mind, this paper investigates whether or not English language teachers in Serbia incorporate tasks at different levels of cognitive capacity in their tests so as to monitor and improve their students' domain-specific CT skills. The authors gathered 28 English language tests constructed by 14 teachers and classified the tasks according to the six levels of Bloom's Taxonomy. The analysis revealed that the tasks for the fiftfifth grade include mostly tasks at the lowest level of the taxonomy, whereas those for the sixth grade are predominantly at the levels of understanding and application. Tasks requiring complex cognitive reasoning were shown to be rather scarce, which indicates that teachers do not assess students' free and creative use of the foreign language, i.e., complex reasoning skills. It is advisable that English language teachers be trained in the very concept of CT and its successful teaching and testing principles.